2017
DOI: 10.1186/s13071-017-2144-2
|View full text |Cite
|
Sign up to set email alerts
|

Stage and tissue expression patterns of Schistosoma mansoni venom allergen-like proteins SmVAL 4, 13, 16 and 24

Abstract: Background Schistosoma mansoni venom allergen-like protein (SmVAL) is a gene family composed of 29 members divided into group 1 encoding proteins potentially secreted, and group 2 encoding intracellular components. Some members were found to be upregulated in the transition of germ ball - cercariae - day 3 schistosomula, suggesting that group 1 SmVAL proteins are associated with the invasion of the human host, although their functions are not completely established. Recently, we have described the localization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
22
1
4

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(29 citation statements)
references
References 49 publications
2
22
1
4
Order By: Relevance
“…In addition, we supported the discovery of SmVAL22 preferential expression in sporocyst ). SmVAL1 and SmVAL24 were found to be nearly exclusively in cercaria, which differs from the finding about higher SmVAL24 expression in the germ balls (Fernandes et al 2017). More interestingly, we discovered two VALs that seem exclusive for the testis, whose functions need further investigations.…”
Section: Discussioncontrasting
confidence: 99%
“…In addition, we supported the discovery of SmVAL22 preferential expression in sporocyst ). SmVAL1 and SmVAL24 were found to be nearly exclusively in cercaria, which differs from the finding about higher SmVAL24 expression in the germ balls (Fernandes et al 2017). More interestingly, we discovered two VALs that seem exclusive for the testis, whose functions need further investigations.…”
Section: Discussioncontrasting
confidence: 99%
“…Despite the abundance of group 1 SmVALs in these important life stages, the understanding of SmVAL function remains somewhat limited. A lipid-binding function was demonstrated for SmVAL4 (Kelleher et al, 2014), a plasminogen-binding function was revealed for SmVAL18 (Fernandes et al, 2017) and a host matrix metalloprotease modulatory function detected for SmVAL9 (Yoshino et al, 2014). The group 2 protein SmVAL6 has recently been shown to be a target for IgE, IgG4 and IgG1 responses in infected individuals, indicating that the SmVALs may influence the immune response (Farnell et al, 2015).…”
mentioning
confidence: 97%
“…Schistosoma mansoni cercariae, schistosomula, adult worms, eggs, miracidia and mother sporocysts (24 h and 96 h sporocysts) were obtained as previously described (Chalmers et al, 2008). Germ balls were obtained as previously described (Fernandes et al, 2017).…”
mentioning
confidence: 99%
“…It has been described that parasite infections can develop a strong response and high levels of IgE in allergic sufferers, i.e., asthma or tropical pulmonary eosinophilia [ 28 , 29 , 30 , 31 ]. Moreover, it seems that infections by A. lumbricoides, T. canis, T. trichiura , hookworm, and S. mansoni can cause allergic reactions in humans [ 15 , 16 , 17 , 18 , 19 ]. This has also been described for different types of human filariasis [ 32 ] and specifically regarding heartworm, there is some evidence that indicates that this parasite might also have the same capacity [ 21 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown the role of some helminth parasites in the development of allergic processes in humans, and have shown associations between allergic sensitization (i.e., to mites) and seropositivity to parasites, such as Ascaris lumbricoides , Toxocara canis, Trichuris trichiura , hookworm, and Schistosoma mansoni [ 15 , 16 , 17 , 18 , 19 ]. Furthermore, there is evidence that some filariae, such as D. immitis , may influence the development of hypersensitivity in people [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%